APPLICATION OF GERMAN COMIC MEDIA THROUGH THE MAKE BELIEFS COMIX WEBSITE FOR GERMAN WRITING SKILL AT SMAN 9 MALANG - Azizah, Isnaini Nur (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2024)
This study aims to describe the application of German comics media through the Make Beliefs Comix Website for German writing skilln and students' responses to the application of the media. The research method is descriptive qualitative with 36 students and two observers as the data sources. The data were obtained from the results of questionnaires and observation. Based on the questionnaires result, it shows that the application of German comics media through Make Beliefs Comix receives positive response from students. Based on the results of observation, the students shows enthusiasm in making comics through Make Beliefs Comix. Furthermore, the application of media through Make Beliefs Comix is interesting for students and can increase their enthusiasm for learning. Keywords: learning media, comic, Make Beliefs Comix, writing skill